2014
DOI: 10.1111/jac.12065
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Agriculture – A Portuguese Case Study

Abstract: This paper gives a glance about the conservation agriculture concept and the worldwide increase in agricultural area where this technique has been adopted. The main constraints to agricultural production in the Mediterranean region are discussed, highlighting the importance of conservation agriculture to mitigate them. Results of long-term studies with this technique, in Portugal, showed an increase in organic matter, improvement of aggregates stability and continuity of biological porosity along the soil prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 5 publications
2
15
0
Order By: Relevance
“…Sometimes they had experienced consequences of unexpected extreme rainfall. This finding is similar with [27] where the authors identified most climatic variation in rainfall.…”
Section: Climate Changesupporting
confidence: 89%
“…Sometimes they had experienced consequences of unexpected extreme rainfall. This finding is similar with [27] where the authors identified most climatic variation in rainfall.…”
Section: Climate Changesupporting
confidence: 89%
“…The adequate availability of fertilizers can be particularly important in areas with inherently low soil fertility where the production of sufficient quantities of crop residue for soil protection is difficult (Giller et al, 2015;Thierfelder et al, 2018). The presence of protectionist mechanisms, such as subsidies for the production of certain commodities, can also hinder adoption as these do not encourage the reduction of production costs and can act to decrease the profitability of CA practices (Carvalho and Lourenco, 2014;Tekle, 2016).…”
Section: Economic Challengesmentioning
confidence: 99%
“…In this case, and contrary to what happened in the previous experiment, the Cq value is significantly greater under minimum tillage ( Table 2). Keeping in mind that conservation agriculture is based on no-till, maintenance of crop residues on the soil surface and crop rotation [47,48], these results highlight the need to increase the use of conservation agriculture practices to reduce the incidence of the disease. When a mycotrophic cover crop is used, beside many other benefits, it allows the development of the ERM, that if kept intact, will promptly colonize the following crop.…”
Section: Discussionmentioning
confidence: 99%